Chapter 5 Cognitive-communication difficulties in adults with Long COVID - Cummings, Louise (Taylor & Francis, 2023)
This collection is the first of its kind to examine the impact of the COVID-19 pandemic on the caseloads and clinical practice of speech-language pathologists. The volume synthesises existing data on the wide-ranging effects of COVID-19 on the communication, swallowing, and language skills of individuals with COVID infection. Featuring perspectives of scholars and practitioners from around the globe, the book examines the ways in which clinicians have had to modify their working practices to prioritise patient and clinician safety, including the significant increase in the use of telepractice during the pandemic. The volume also reflects on changes in training and education which have seen educators in the field redesign their clinical practicum in order to best prepare students for professional practice in an age of COVID-19 and beyond, as the field continues to grapple with the long-term effects of the pandemic. Offering a holistic treatment of the impact of COVID-19 on the work of speech-language pathologists, this book will be of interest to students, researchers, and clinicians working in the discipline.